Studying the effect of second-class current on polarization degree of photon in free neutron β decay - موسى محمد; معلا تيسير; ديب ماوية (Latakia University Journal -Basic Sciences Series, 2020)
We concentrated our attention in this research on the effect of the second class currents (tensoric component ) on the most important physical parameter that describes the photons associated - of the free neutron, which is the degree of its polarization . Therefore a mathematical equation was extracted for the probability of the decay , with the release of the electron an X-ray photon (Bremsstrahlung), taking into account the second class currents (tensoric component ). Then We extracted the mathematical equation that determines the degree of polarization of the released photon , which allowed us to show the role of the type of the photon polarization (right , left ) on the polarization degree connected to the photon’s energy , as we showed in Graphs. The effect of the component on was estimated, it was found to be in the case , and in the case in the energy range .